Hajizada , Mahmud - (:unkn) unknown (My University, 2026)
Mahmud Hajizada graduated with honors from the Faculty of Civil Engineering of the Azerbaijan University of Architecture and Construction in 2011, earning a Bachelor's degree in Industrial and Civil Construction Engineering. He received an MBA in Management with honors from the Azerbaijan State University of Economics in 2014 and obtained a Bachelor's degree in International Relations from the Academy of Public Administration under the President of the Republic of Azerbaijan in 2021. In 2017, he was awarded the degree of Doctor of Philosophy (PhD) in Economics after successfully defending his dissertation entitled Information Economy and Its Development Trends in Azerbaijan. Dr. Hajizada has held various positions in public administration and the energy sector, including roles at the Ministry of Communications and High Technologies of the Republic of Azerbaijan, the Innovation Agency, and Azərenerji OJSC, where he currently serves as Deputy Head of the Department of Foreign Economic Relations. Since September 2024, he has been a Lecturer at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction, teaching Strategic Management and Business Relationship Management. He is the author of 15 scientific publications, several of which have appeared in international peer-reviewed journals, and serves as a member of the Editorial Board of the international scientific journal Proceedings. His research interests include information economics, digital transformation, strategic management, international economic relations, innovation policy, sustainable economic development, and energy economics.